Pengaruh Kepercayaan Teknologi Sistem Informasi Akuntansi Dan Kepuasan Pengguna terhadap Kinerja Individual - Latuz Zaroh, Evi; suyanto, suyanto; Kurniawan, Angga (Universitas Muhammadiyah Metro, 2024)
This study aims to examine the effect of Accounting Information System Technology Trust and User Satisfaction on Individual Performance (Case Study of Employees at the Metro City Regional Financial and Asset Management Agency Office). This research uses the Technology Acceptance Model (TAM) theory. This research method uses non-probability sampling method with purposive sampling technique. The number of samples used in thus study were 59 respondents with the criteria of employees at the criteria of employees at the Metro City Regional Financial and Asset Management Agency office who were familiar with the Accounting Information Technology System. The tool to be used for data analysis is multiple linear regression analysis. The results of this study indicate that: (1) Technology Trust in Accounting Information System has a positive effect on individual performance. (2) User Satisfaction has a positive effect on individual performance. (3) Together, the variables of Accounting Information System Technology Trust and User Satisfaction simultaneously have a positive effect on Individual Performance at the Metro City Regional Finacial and Asset Management Agency.